THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, COMPETENCE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE OF PT WASKITA KARYA (PERSERO) TBK IN BECAKAYU 2A UJUNG PROJECT - Sudiarso, Sudiarso (Dinasti International Journal of Management Science, 2022)
Uncertain economic conditions in Indonesia, have an impact on the performance of PT. Waskita Karya (Persero) Tbk which experienced a decline. The decline in performance was due to the performance of several projects belonging to PT Waskita Karya (Persero) Tbk not meeting production targets such as the Becakayu Project Section 2A Ujung. This study aims to determine the effect of Transformational Leadership, Competence, and Work Environment on Employee Performance at PT Waskita Karya (Persero) Tbk Becakayu Project Section 2A Ujung. This study used the sample of 60 respondents which were then analyzed by using SEM PLS and correlation matrix between dimensions. This study resulted in Transformational Leadership and Competence having a significant effect on employee performance, while the work environment had no effect on employee performance. However, the three variables simultaneously have a significant effect on employee performance.